INTEGRASI METODE TILAWATI DAN TAHFIDZ DALAM PEMBELAJARAN AL-QURAN DI SDIT MUJAHIDUL AMIN - Putri, Cindy Marcellina; Hikmah, Nurul (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study applies a qualitative field approach to analyze the application of the Tilawati method and Tahfidz program in an integrated manner in learning the Qur'an at SDIT Mujahidul Amin. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results revealed that the school implemented an integrated learning model with a clear division of tasks between Tilawati teachers who teach reading the Qur'an systematically and Tahfidz teachers who are responsible for the memorization program. The integration of the two methods is done sequentially and in parallel according to the ability of each student. The success of the program is supported by regular training for teachers and the implementation of a gradual learning strategy (tadarruj), resulting in students successfully achieving the Juz 30 memorization target, some even exceeding it. This integration model is recommended as an effective option for Islamic education institutions in organizing comprehensive and sustainable Qur'anic learning.